Pemberdayaan Kelompok Tani Desa Salenrang melalui Diversifikasi Olahan Tanaman Pappa (Stenochlaena palustris) (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program (PKM) aims to empower farmer groups and women’s groups in Salenrang Village, Bontoa District, Maros Regency, through the diversification of pappa plant (Stenochlaena palustris) products. The pappa plant is a local resource with high economic potential, yet its utilization remains limited. Therefore, this PKM activity focuses on enhancing community skills in processing pappa leaves into innovative food products with greater market competitiveness. The program was carried out through counseling, practical training, and intensive mentoring from upstream to downstream. Participants were guided in selecting high-quality raw materials, applying hygienic processing techniques, creating recipe innovations, developing attractive packaging, and strengthening business management as well as digital-based marketing strategies. Through a participatory approach, the program not only increased knowledge but also built technical skills that could be directly applied in local businesses. The results of the activities indicated a significant improvement in the knowledge and skills of approximately 25 participants. One of the flagship products developed was pappa leaf crackers, which are characterized by a crispy texture and distinctive taste. The product received positive responses from the local community and showed promising market potential. At least 15 group members were intensively trained and expressed strong interest in developing entrepreneurial activities based on pappa leaf processing. This program contributes to strengthening household economies, preserving local plants as part of cultural identity, and promoting regional culinary development. With continued mentoring, pappa-based processed products are expected to become an icon of creative economy in Salenrang Village and foster sustainable community independence.